2004
DOI: 10.1007/s00122-004-1672-2
|View full text |Cite
|
Sign up to set email alerts
|

Genomic organization of the complex α-gliadin gene loci in wheat

Abstract: To better understand the molecular evolution of the large alpha-gliadin gene family, a half-million bacterial artificial chromosome (BAC) library clones from tetraploid durum wheat, Triticum turgidum ssp. durum (2n = 4x = 28, genome AB), were screened for large genomic segments carrying the alpha-gliadin genes of the Gli-2 loci on the group 6 homoeologous chromosomes. The resulting 220 positive BAC clones--each containing between one and four copies of alpha-gliadin sequences--were fingerprinted for contig ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 46 publications
2
54
0
1
Order By: Relevance
“…Gu et al (2004) indicated that the B genome diverged before the separation of the A and D genomes. There has been considerable controversy over the donor of the S-genome progenitor, but it was correctly identifi ed as an ancestor of Ae.…”
Section: Origin Of the B Genomementioning
confidence: 99%
See 4 more Smart Citations
“…Gu et al (2004) indicated that the B genome diverged before the separation of the A and D genomes. There has been considerable controversy over the donor of the S-genome progenitor, but it was correctly identifi ed as an ancestor of Ae.…”
Section: Origin Of the B Genomementioning
confidence: 99%
“…However, the various wheat genomes and the rice genome appear to have similar genetic composition with a good macrolevel syntenic relationship (Gale and Devos 1998;Sorrells et al, 2003;Tang et al, 2008). Flavell et al (1974) and Gu et al (2004) established that over 80% of the hexaploid wheat genome comprised noncoded highly repeated DNA sequences and highly active and nonactive retrotransposons. The intergenic regions (Bennetzen 2000;Feuillet and Keller 2002;Wicker et al, 2003) and genic regions (Gu et al, 2004) of many species are mainly composed of retrotransposons, and the vast numbers of these retrotransposons are correlated with genome size (Kidwell et al, 2002).…”
Section: Genome Evolution and Modificationmentioning
confidence: 99%
See 3 more Smart Citations